Produção de bloco de gesso e cinzas de carvão mineral aditivados com sal orgânico à base de óleos vegetais. - Amaral, Rafael Filgueira (2023)
One of humanity's great challenges is to rationalize the use of environmental resources, so as not to compromise the existence of future generations – elaboration of sustainable processes and products. Gypsum has properties such as the availability of cheap raw materials, volumetric stability, acoustic and thermal insulation, fire resistance, low toxicity, however, it has low resistance to water absorption. The objective of this research was to rationalize a production process for the separation of gypsum and mineral coal ash, added with an organic salt based on essential oils, commercially known as DS-328 (Synthetic Termite Sludge) and Sulfate of Aluminum. This additive was used with a view to using partition blocks, based on plaster, for wet areas in buildings. An essential reason for reducing the amount of gypsum was to ensure that the semi-hydrate content in the gypsum was equal to or greater than 85.0%. The properties of the specimens made were evaluated with the aid of an experimental design of the type Rotational Composite Design (DCCR), through the application of the STATISTICA software from StatSoft, Version 12. The proposed composite had its specimens from the hardening of the paste with a water/plaster ratio of 60% m/m (< water/plaster content than the conventional one). The composite formulation showed dependence with the type of response variable. Thus, on average, values of: setting time (TP) = 10.15 min; Resistance to pain (RC) = 13.29 MPa e; Water absorption (AA) = 11.65%. The addition of DS-328, chemically aided with commercial aluminum sulfate (chemical stabilization function), increased the strength resistance and improved the hydrophobic character of the composite in relation to the properties of pure gypsum. The results obtained with the gypsum-CCM mixture added with DS-328 led to a reduction in gypsum consumption through the use of mineral coal ash (environmental liability), giving rise to a new material for separation blocks for ecological areas.